Strategic Planning and Product Portfolio Development at Umrah Al Hijrah Travel Agents in the Era Digital Competition in the Surabaya Area - Zahra, Nasywa Aulia Isna; Karmila, Iva; S, Yeni Aprilia; Ramadhan, Givaldi; Najah, Rizka Hidayatun; Andriansyah, Muhammad Farhan; N, Rusdi Hidayat; Ikaningtyas, Maharani (Journal of Business and Halal Industry, 2025)
The Umrah travel industry in Indonesia has undergone significant transformation along with the development of digital technology. The emergence of app-based travel agencies and digital platforms has created disruption to conventional Umrah travel business models. This research aims to analyze how strategic planning and product portfolio development can be effectively implemented by Al Hijrah Umrah travel agents in facing the era of increasingly fierce digital competition. This study employs qualitative research methodology with in-depth interview techniques and direct observation of Al Hijrah's promotional activities and services on social media and digital platforms. Primary data was obtained from Al Hijrah's management and operational staff, while secondary data came from internal company documents and related literature. The research results show that Al Hijrah has implemented digital transformation through various platforms such as Instagram, TikTok, and WhatsApp Business, and developed an official website with live chat features and digital payment systems. The company also diversified its products by offering thematic packages such as Millennial Umrah, VIP Umrah, and Umrah Plus Turkey. SWOT analysis reveals that Al Hijrah's strength lies in its good reputation and strong relationships with partners in Saudi Arabia, but faces challenges in limited digital technology expertise. Market response to Al Hijrah's digital innovation has been very positive, especially from the 25-40 age group. This research concludes that the implementation of adaptive strategic planning and market-oriented product portfolio development is key to success in digital competition, by utilizing CRM technology, online reservation systems, and integrated digital marketing strategies.